Interpretação pragmática: uma contribuição para a análise do discurso jurídico - Silva, Roberto Carlos (2011)
This work presents an analysis of the interpretation of legal discourse that highlights features of pragmatics, with emphasis on a topical-rhetorical approach of the normative text. The proposed discussion takes into account theoretical features of the pragmatics field, analyzing its presence as one of man´s concerns for a long time. It reveals its characterization and then proceeds with the indication of the essential elements of rhetoric, with Chaïm Perelman, and topic with Theodor Viehweg. The study undertaken in two author´s work stays limited to the exposure of rupture the mathematical logic and the proposition of forming a rationality adequate to law. It also deals with notions related to the communicative situation and the need of proof presentation, as well as the foundation of the philosophy of law as a research basis pointing to a theory of argumentation. Its take the doctrine of discourse to explain its elements and pragmatic functions, transposing it to the legal discourse. There is an Endeavour to report the minimum elements for a definition of legal interpretation, while the main characteristics are emphasized. It goes on dealing with the initial analysis of the presence of legislative intent in the interpretation process, proceeding with the investigation of the relationship of the power of symbolic violence. It establishes the analysis of the rational legislator's construct to give basis to a juridical rationality fit to value the pragmatics aspect of language; it reopens the debate of what one searches in the act of interpreting, between the will of the legislator and of the law. It becomes present the possibility of dealing with such a question pragmactically, without adhering to one or other position, that could be called ideological. In order to make explicit the construction of law pragmatic interpretation, the interpreter proceeds carefully in the analysis of the clarity and doubts of juridical interpretation. Finally, this work presents the technical rules used in law in the search of decidability, explaining the syntactic, semantic and pragmatic nature. The object aimed is the analysis of juridical discourse and language through the explicit option of topic-retoric, in the purpose of giving basis and appealing to the interpretation that takes into account the pragmatic aspect of the language. The chosen method is monographic-descriptive, through the exam of literature and documents. The final part of this work tries to demonstrate the viability and relevance of the inclusion of the pragmatic element as essential to the interpretation of legal texts